Change and continuity in the lithic technologies from Final to Ceramic Final Later Stone Age,Limpopo Basin, South Africa - Guillemard, Iris (My University, 2020)
The late Holocene of southern Africa is a key period of social and economic change. From around two thousand years ago, the appearance of domesticated sheep and pottery at Later Stone Age (LSA) sites, traditionally associated with hunter-gatherers, marks the beginning of varied neolithization processes. The Limpopo River Basin is particularly important to the discussion of these processes. The area is thought to have been a major route of migration and settlement for varied populations, generally classified as ‘hunter-gatherers’, ‘herders’ and ‘farmers’. These three economic categories are often associated with specific language groups. This association leads to the creation of paradigms, that sometimes impede our understanding of social dynamics during the late Holocene. This thesis aims to investigate phenomena of stability and change in lithic systems through the late Holocene within the socially complex middle Limpopo River Basin. It begins with a case study of the microlithic assemblage from Balerno Main Shelter (BMS), dated from 300 BC to the second millennium AD. The lithic technical system is defined using the chaîne opératoire and techno-functional methods and investigated to determine if change or stability can be observed throughout the sequence. Hypotheses are then formulated about the scenario observed, in relation to the potential economic and social shifts that occurred within hunter-gatherer societies. The potential trans-economical nature of lithic technologies is considered, along with phenomena of interactions in the Limpopo River Basin. Lastly, large-scale technological phenomena are discussed, and the thesis questions what techno-complexes could represent beyond the classic vision of ‘archaeological cultures’. A discussion is then opened about multi-disciplinary migration models that equate subsistence, language and genes in the context of the pastoral Khoe migration in southern Africa. Rather than correlating different ‘traits’ within ‘culture container models’, as per convention, this thesis proposes a dis-assembling of these characteristics for the investigation of the reason for change or stability within each analytical category. This disassembling allows us to go beyond simplistic correlations to investigate phenomena of co-dependence or independence between different proxies and factors using varied hypotheses
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, in fulfilment of the requirements for the degree of Doctor of Philosophy, 2020